Facilitating Positive Washback through Authentic Assessment in EFL Assessment - Arief Eko Priyo Atmojo (Acitya: Journal of Teaching and Education, 2021)
Washback has become a main concern for researchers in the field of language testing proven by numerous studies which have been done. The degree, nature, and scope of washback depend on the kinds of tests employed and the contexts where the tests are administered. This present article is aimed at discussing how authentic assessment brings positive washback in EFL assessment. It is only a literature review, not an empirical research article. This article limits and focuses the discussion on the washback at micro level which means the test effects on teaching and learning at classroom level. It addresses how authentic assessment leads to positive washback in EFL assessment. It also discusses how each form of authentic assessment can uniquely generates positive washback in EFL assessment. In conclusion, authentic assessment brings positive washback in EFL classes. It links classroom instructions to students’ real-world experiences. It is suggested for EFL teachers to be literate of how to facilitate positive washback in EFL assessment and how to employ authentic assessment in assessment practices. Some kinds of further researches are also encouraged.